VARIABILITY OF THE WINTER SNOWINESS AT THE SOUTHEAST OF KAMCHATKA PENINSULA - A. A. Grits (Лëд и снег, 2015)
Analyses of the snow cover depth for several years in the southeast ofKamchatkaPeninsulashow some possibilities for development of skiing, tourism and mountaineering. We found four types of winters in 1935–2006: high-snowy, mid-snowy, little-snowy, and unstable snowy. The average depth of snow for 71 years is133 cmwith minimum of60 cmin 1939 and maximum of272 cmin 2005. The exceptional snowiness gives opportunity to use this territory even in summer months. In some years inKamchatka, the mountain-skiing season lasts a round year. The average date of forming the steady snow cover in the lowlands areas is November 12, and the middle date of the highest snow is May 22. The most comfortable time for recreation on the peninsula in wintertime are observed from the middle of March until the middle of April. During this time, we have the maximum snow, large duration of sunshine and air temperature closed to zero degrees.